2018
DOI: 10.3892/ijmm.2018.3944
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient method for isolating urinary exosomes

Abstract: In the present study, a highly efficient method, referred to as optimized ultrafiltration (OUF), was developed. This method is effective for exosome purification and also facilitates clinical work involving substantial urinary exosome isolation. In the OUF method, 0.22-µm filters along with a dialysis membrane with a molecular weight cut-off of 10,000 kDa were introduced, in order to remove extracellular microvesicles that were >200 nm and concentrate the supernatant up to 1/50 of the initial volume. The exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 41 publications
2
67
0
Order By: Relevance
“…NVs were isolated by ultracentrifugation. Although it was reported that the amount and profile of the obtained NVs should depend on the isolation method (31), the size of the particles isolated in the present study was similar to that described in previous reports (14,15), indicating successful NV purification. No changes were detected in urinary NV excretion or particle size profiles in the PAN nephritis model.…”
Section: Discussionsupporting
confidence: 87%
“…NVs were isolated by ultracentrifugation. Although it was reported that the amount and profile of the obtained NVs should depend on the isolation method (31), the size of the particles isolated in the present study was similar to that described in previous reports (14,15), indicating successful NV purification. No changes were detected in urinary NV excretion or particle size profiles in the PAN nephritis model.…”
Section: Discussionsupporting
confidence: 87%
“…SEC has proven to be beneficial in the elimination of contaminants such as proteins and lipoproteins [177]. Lastly, ultrafiltration involving the use of membranes with specific pore size is a suitable approach for rapid EV purification from large volume samples and allows a high degree of purification when it is combined with SEC [178,179,180].…”
Section: Evs As Potential Therapeutic Targets For Bamentioning
confidence: 99%
“…At present, ultracentrifugation is the most convenient and economical method for EVs detection. However, ultracentrifugation can damage EVs and lead to relatively low yields and recovery rates 40 . Differential centrifugation is the "gold standard" for purification of EVs, but it is time-consuming 41 .…”
Section: Components Of Urine Biopsymentioning
confidence: 99%
“…Membrane filters consist of many well-defined pores, where particles smaller than the pores can pass through them and particles larger than the pores are captured on the membrane 58 . Some studies have reported the use of membrane filters to isolate urine biomarkers such as EV and BC cells 59 , 60 . However, whether at the micron or nanoscale, the filtration technology is often hindered by technical issues such as biofouling, low throughput, need of skilled handling and may damage rare cells in the process 61 .…”
Section: Current Technologies For Urine-based Biomarkersmentioning
confidence: 99%